Feasibility Of Developing An Augmented Reality (AR) Science Module With Audio Integration Using Assemblr Edu: A Case Study On Matter And Its Changes - Arlin Maya Sari; U M Dewi; F Fanita; S B Dwiardi (LPPM Universitas Malikussaleh, 2024)
The study aims to evaluate the feasibility of Augmented Reality (AR)-based science learning media with audio features, using the 4D development model (Define, Design, Develop, Disseminate). The media was developed to facilitate more interactive and immersive science learning through AR visualizations and audio explanations that assist in understanding complex concepts. The development stages include: (1) Define, to analyze the needs and learning objectives; (2) Design, to design AR and audio-based media; (3) Develop, to create the media prototype and conduct feasibility tests through validation by subject matter and media experts; and (4) Disseminate. Data were collected through questionnaires and observations, then analyzed descriptively. The evaluation results show that the learning media was rated as